Effect of resistance ladder training on sparc expression in skeletal muscle of hindlimb immobilized rats. Issue 6 (4th February 2016) - Son, Jun Seok; Kim, Jang Hoe; Kim, Hee‐Jae; Yoon, Dong Hyun; Kim, Jin‐Soo; Song, Han Sol; Song, Wook
ABSTRACT: Introduction: Secreted protein acidic and rich in cysteine (SPARC) is associated with skeletal muscle atrophy. Here we examined possibility that resistance training could regulate SPARC expression in muscle atrophy in an immobilized hindlimb model. Methods: Sprague‐Dawley rats underwent resistance ladder training and hindlimb immobilization. Cross sectional area and grip strength were measured. SPARC protein levels in the plantaris and soleus, and serum after exercise and immobilization were then analyzed. Results: Resistance training decreased body weight ( P  < 0.001) and increased muscle quality ( P  < 0.001). In the plantaris, muscle atrophy (31.82%) and up‐regulated SPARC expression ( P  < 0.05) after immobilization were alleviated by resistance training. Conclusions: Resistance training led to suppression of SPARC expression in the plantaris and showed a pretraining effect in atrophied rat muscle. Thus, SPARC may play a pivotal role in muscle homeostasis. Muscle Nerve 53 : 951–957, 2016